If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 5b = -1 Solving 6a + 5b = -1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5b' to each side of the equation. 6a + 5b + -5b = -1 + -5b Combine like terms: 5b + -5b = 0 6a + 0 = -1 + -5b 6a = -1 + -5b Divide each side by '6'. a = -0.1666666667 + -0.8333333333b Simplifying a = -0.1666666667 + -0.8333333333b
| 7y+y= | | 2(3x-6)+10=-4x+8 | | m-(-12)=22 | | 5z=91 | | 6+5x=61 | | 3x^2-4x=4 | | 2x=37 | | -2x^2+12x-12=0 | | 4x+3=51 | | 3y=73 | | 3(4y+19)=33 | | 6x+7=79 | | 3x+10=-107-10x | | -2(x+1)=10 | | n+(-28)=0 | | 8n-2n= | | 3x^2-24x+36=0 | | 3(3x-2)=39 | | 9+3x=24 | | 6(8)-6=54 | | 3x+2x-1=9 | | 6x-y=54 | | 6+4x=26 | | 8+3x=41 | | 5+5x=45 | | 2+7x=51 | | 4x-2=5x-8 | | x^2+3x+9= | | 5+2x=21 | | 9+7x+4x=31 | | 4k=3(k+2)-2k | | 5x+6+5x=106 |